2019
DOI: 10.1007/s10340-019-01166-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation modulates both constitutive and inducible plant defenses against thrips but is dose and plant genotype dependent

Abstract: Ultraviolet (UV) radiation has emerged as an environmental cue with potential uses to enhance plant protection against arthropod pests in agriculture. UV can augment constitutive and inducible plant defenses against herbivorous arthropods. Here we investigated whether application of supplemental UV to chrysanthemum (Chrysanthemum × morifolium Ramat) cuttings during their rooting phase enhanced plant resistance to an important insect pest, Western flower thrips (Frankliniella occidentalis). For this, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…UV-B radiation is also emerging as an environmental cue that can upregulate plant defences against herbivorous arthropods. For example, short daily exposures of UV radiation increased the resistance of chrysanthemum ( Chrysanthemum × morifolium ) to the insect pest, thrips ( Frankliniella occidentalis ) [ 210 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…UV-B radiation is also emerging as an environmental cue that can upregulate plant defences against herbivorous arthropods. For example, short daily exposures of UV radiation increased the resistance of chrysanthemum ( Chrysanthemum × morifolium ) to the insect pest, thrips ( Frankliniella occidentalis ) [ 210 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…A strong reduction of thrips silver damage was reported by Escobar-Bravo et al (2019a) using the same UV-B intensity in tomato as in our trial. Doubling of this UV-B intensity was needed to increase resistance to thrips in chrysanthemum whereby effects were genotype dependent ( Escobar-Bravo et al, 2019b ). Although eggplant belongs to the plant family of the Solanaceae, as does tomato, it appears that UV-B treatments to increase host plant resistance may be species specific, especially seen in the relatively low window of effective UV-B ranges ( Escobar-Bravo et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2020) recently reported that the application of jasmonic acid to all leaves or only the apical leaves of chrysanthemums (Chrysanthemum × morifolium) increased the resistance to thrips, whereas the application to basal leaves was not v www.esajournals.org effective against the thrip pest (Chen et al 2020). Extra doses of ultraviolet radiation can induce defenses mediated by jasmonic acid, thereby increasing the resistance to thrips in Chrysanthemum × morifolium (Escobar- Bravo et al 2021). The dosage depended on time and genotype but demonstrated the possibility of some management strategies to efficiently stimulate natural plant defenses against arthropod herbivores.…”
Section: General and Significant Changes Observed In Metabolomic Analyses Of Plant Foliar Metabolism Related Tomentioning
confidence: 99%
“…Our synthesis of results from studies that have used metabolic platforms to investigate constitutive and inducible defenses against herbivorous attack at the level of metabolomic profiles clarifies the more widespread changes to metabolic pathways used across several plant species to minimize the negative effects of herbivore. Few studies, however, using metabolomics platforms have compared various constitutive and inducible defenses at once among plant genotypes in response to attacks by the same herbivore (Sato et al 2013, Cai et al 2017, Escobar-Bravo et al 2021, Perez-Fons et al 2019. Untargeted analyses that used ecometabolomics have demonstrated a large chemical diversity that can structure natural communities into metabolic subgroups to create high small-scale heterogeneity for specialized herbivores (Clancy et al 2017).…”
Section: General and Significant Changes Observed In Metabolomic Analyses Of Plant Foliar Metabolism Related Tomentioning
confidence: 99%